(untitled) (MAUSAM, 2002)
In the present paper performance of the monthly sub-divisional summer monsoon rainfall is studied in association with the position of the Low Pressure System (LPS) over the Indian region. Existence of the LPS over a particular location increases the rainfall activities in certain parts of the country while decreases in some other parts. For this study, the Indian region (5°-35° N and 60° -100° E) is divided into 5° Lat. ´ 5° Long. grids. The duration of LPS is taken in terms of LPS days with respect to the location of LPS in a particular grid. Monthly total number of LPS days in each of the grids are computed during the summer monsoon season, June to September for the period 1891 – 1990. Maximum number of LPS days (more than half of the total) are observed in the latitude belt between 20°-25°N. The percentages of total LPS days in this area are higher in July and August which are peak monsoon months as compared to June and September. When there is a LPS are in the area 20°-25° N and 80°-90° E, there is significant increase in the rainfall activities in the sub-divisions along mean monsoon trough while northeast India and southeast peninsular India experience significant decrease in rainfall in the months of July and August. Owing to the movement of LPS from east to west through central India, most parts of the country, excluding northeast India and south peninsular India get good rainfall activity. Correlation coefficients between monthly LPS days over the different grids and monthly sub-divisional rainfall are computed to study the relationships. The performance of sub-divisional rainfall mostly related with the occurrence of LPS in certain grid- locations. The correlation field maps may give some useful information about rainfall performance due to LPS in a particular grid locations.